Research on the Path of Integrating Chinese Dance Movement Elements into Sports Dance - Liu, Ruonan (International Journal of Social Sciences and Public Administration, 2024)
This paper studies how the movement elements of Chinese dance are integrated into sports dance, and discusses the path of integration. By analyzing the characteristics of traditional Chinese dance and the requirements of sports dance, it is found that there is a certain fit between the two. In the context of cultural inheritance and innovation, this article proposes some feasible paths, including cultivating the cross-domain ability of dance coaches and athletes, strengthening the cross-integration of dance and physical education, and promoting innovative dance creation. These paths are expected to promote the better integration of Chinese dance movement elements in sports dance, and provide new ideas and methods for the development of Chinese sports dance.